Hubungan Kepemimpinan Inklusif, Keterlibatan Karyawan, Efikasi Diri terhadap Perilaku Kerja Inovatif - Nicolas Acarya Prasida Caitanya; Mansyur, Anwar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the relationship between inclusive leadership variables, employee involvement, self-efficacy and innovative work behavior. Because currently employees of a company are required to be more creative and active in carrying out their work. If employees are equipped with innovation, they will easily solve problems that exist internally and externally to the company. This research uses a saturated sampling technique, which means that all existing populations are included as research objects. Questionnaires were distributed directly and data was collected from 105 employee respondents. The results of research using SPSS showed that inclusive leadership on innovative work behavior had a significant effect and had a positive impact, employee involvement in innovative work behavior had no significant effect and had a negative impact, self-efficacy on innovative work behavior had a significant effect and had a positive impact.